The effect of in-season demands on lower-body power and fatigue in male collegiate hockey players - Whitehead, P. N.; Conners, R. T.; Shimizu, T. S. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to determine the effect of in-season demands, such as games, travel, and the subsequent fatigue related to these demands, on lower-body power (LBP) in collegiate hockey players. Two jump protocols (countermovement and squat jumps) were used to calculate LBP. Twenty-seven NCAA (National Collegiate Athletic Association) Division I male hockey players (age, 21.9 ± 1.4 years; height, 176.7 ± 6.5 cm; body mass, 81.4 ± 7.9 kg) participated in the study that spanned 18 weekly sessions. At each session, participants completed an 8-item fatigue questionnaire, which provided a cumulative numerical value for fatigue (total score of fatigue [TSF]), before performing maximal jumps on a contact mat. General linear modeling was conducted to compare dependent variables (jump height, relative LBP, TSF) across weekly sessions. Pearson product-moment correlation coefficients were calculated to examine the relationship between jump height and LBP across the jump protocols, as well as to examine the relationship of TSF with all measured variables. Jump height and LBP declined throughout the season with greater effect of travel observed following the longest travel sequence (p = 0.05; Eta2 = 0.60). Differences in TSF were observed from baseline (p = 0.037), and a large effect was seen for away trips that included air travel (d = 1.35). Total score of fatigue had a negative correlation with jump height and power during both jumps (r = -0.742; p < 0.001). In conclusion, the in-season demands of ice hockey resulted in significant reductions in LBP throughout a hockey season, and the 8-item fatigue questionnaire is a sensitive tool reflective of athletic performance measures.